2021
DOI: 10.21511/ppm.19(2).2021.28
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality, employee engagement, and professional commitment: A study of lecturers from Indonesian universities

Abstract: The attention paid by researchers and practitioners to the relationship between employee engagement and spirituality in the workplace is limited, as studies of the two variables still stand alone. This leads to an important and increased emphasis on strength and employee engagement that are built on the organizational culture to show an awareness of spirituality in the workplace. This study aimed to explore the relationship between workplace spirituality and employee engagement of lecturers in Indonesia and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…If the resulting performance criteria are of higher quality, the information obtained from these criteria is more valuable, and as a result, managers are more likely to use these criteria for various purposes, such as evaluating, empowering, and developing employees' careers (Riyanto et al, 2021). The results of many studies show that employee participation in the development of performance criteria has a positive effect on employee job performance (Margaretha et al, 2021). Accordingly, the hypotheses related to the mediating role of the variable of employee participation in the development of performance criteria are as follows: H4: Performance criteria with the aim of evaluating performance through employee participation have a positive and significant effect on the job performance of Keshavarzi bank employees.…”
Section: Mediating Role Of Employee Participationmentioning
confidence: 99%
“…If the resulting performance criteria are of higher quality, the information obtained from these criteria is more valuable, and as a result, managers are more likely to use these criteria for various purposes, such as evaluating, empowering, and developing employees' careers (Riyanto et al, 2021). The results of many studies show that employee participation in the development of performance criteria has a positive effect on employee job performance (Margaretha et al, 2021). Accordingly, the hypotheses related to the mediating role of the variable of employee participation in the development of performance criteria are as follows: H4: Performance criteria with the aim of evaluating performance through employee participation have a positive and significant effect on the job performance of Keshavarzi bank employees.…”
Section: Mediating Role Of Employee Participationmentioning
confidence: 99%
“…In Islam, it promotes employees to be proactive in strategy formulation or planning and empowers their willingness to pursue an organizational vision continuously and constructively (Rana & Malik, 2016). Margaretha et al (2021) analyzed the effect of employee engagement on organizational commitment. The study used data obtained from 322 lecturers who are employed in various universities in Indonesia.…”
Section: Employee Engagement (Eng)mentioning
confidence: 99%
“…As a result, employees who possess high spirituality and work ethic and receive support from their employers are resistant to challenges and possess good attitudes. However, through literature review and demonstration of the relationship between various variables, it was discovered that employee engagement, job satisfaction, and organizational commitment play a mediating function (Athar et al, 2016;Margaretha et al, 2021;Rawwas et al, 2018;Yousef, 2000). To enrich theories as suggested by Khan et al (2010), it is interesting to examine whether they can mediate the relationship between IWV and in-role performance.…”
Section: Mediation Role Of Eng Js and Ocmentioning
confidence: 99%
“…Further, in the West setting, the facets of a nation influence an individual's perception about job crafting and spirituality, while also intrinsically stimulating the person and act as prospective determinant of employee engagement (e.g. Devendhiran and Wesley, 2017;Ghazzawi et al, 2021;Hunsaker and Jeong, 2020;Iqbal et al, 2020;Margaretha et al, 2021;Sharma and Kumra, 2020). The culture of a country in association with spirituality gets exhibited in the behavior and standpoints of employees.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that psychological detachment and job crafting influences organizational and individual outcomes (e.g. Ghazzawi et al, 2021;Hunsaker and Jeong, 2020;Sharma and Kumra, 2020;Iqbal et al, 2020), but there is need to examine the role of psychological detachment and job crafting on employee engagement through unexplored potential determinants such as spirituality and intrinsic motivation (Devendhiran and Wesley, 2017;Margaretha et al, 2021). Ghazzawi et al (2021) studied nurses in Lebanon and observed that employees who are emotionally stable and artistic are capable of efficiently crafting their job.…”
Section: Introductionmentioning
confidence: 99%